Trudności w uczeniu się języków obcych u osób z dysfunkcją słuchu – studium przypadku: uczennica z wszczepionym implantem ślimakowym - Klapa, Julia; Łubiarz, Magdalena (Neofilolog, 2025)
The aim of the article is to present and characterize the difficulties faced by individuals with hearing impairments in learning foreign languages. The basis of the study is an analysis of the foreign language education process, conducted using the example of a high school student with a cochlear implant. The study takes into account the characteristics of communication difficulties experienced by individuals with hearing impairments and their acquisition of foreign language skills. This analysis formed the basis for designing research aimed at collecting data to illustrate the specific challenges in learning foreign languages faced by a person with hearing loss. The research was conducted using a qualitative approach, employing a single case study. The research problems focus on difficulties in learning foreign languages, forms of psychological and pedagogical support, and their evaluation. The study participants include: a third-year high school student, two English language teachers, and one German language teacher. Analysis of the empirical material highlights the difficulties in all language skills reported by the student and observed by the teachers. It also describes the student’s educational background and the forms of support systematically provided by the school, as well as those implemented occasionally in response to immediate challenges.